Improving Critical Thinking Skills and Creativity of Fourth Grade Students in Social Science Using Inquiry Based Learning Model - Rosemey Ratna Purnawati; Maria Melani Ika Susanti; Maria Indarti Rustamti (IJECA (International Journal of Education and Curriculum Application), 2021)
This research aims to improve the critical thinking skills and creativity of social sciences through inquiry based learning in the fourth grade students on one of the  Sleman Private Elementary Schools. This type of research is classroom action research with two cycles. Both cycles consist of two meetings. To collect the data in this research is non-test including observation and questionnaires. The research subjects were fourth grade with a total of 49 students. The initial condition showed that the score of critical thinking skills was 55,72 (fairly critcal category) and the score of creativity skills was 56,33 (fairly creative category). The results showed that the use of inquiry based learning model can improve critical and creative thinking skills. Evidenced by the increase in the score of critical thinking skills in the first cycle was 78,37 (critical category) and in the second cycle was 87,75 (very critical category). In addition, the increase in the score of creative thinking skills in the first cycle was 76,73 (creative category) and in the second cycle it was 85,92 (very creative category).